Improved experimental and diagnostic techniques for dynamic tensile stress–strain measurement with a Kolsky tension bar. (22nd May 2018) - Qiu, Ying; Loeffler, Colin M; Nie, Xu; Song, Bo
Abstract: Kolsky tension bar experiments were improved for dynamic tensile stress–strain measurements with higher fidelity and minimal uncertainties. The difficulties associated with specimen gripping, relatively short gage section, and geometric discontinuity at the bar ends all compromise the accuracy of the traditional strain measurement method in a Kolsky tension bar experiment. In this study, an improved three-channel splitting-beam laser extensometer technique was developed to directly and independently track the displacement of the incident and transmission bar interfaces. By adopting a dual-channel configuration on the incident bar side, the resolution and measurement range of this laser extensometer were coordinated between the two channels to provide highly precise measurement at both small and large strains under high strain-rate loading condition. On the transmission bar side an amplified channel, similar to that used on the incident bar side, was adopted to measure the transmission bar displacement with high resolution. With this novel design, a maximum resolution of approximately 500 nm can be obtained for the bar displacement measurement, which corresponds to a strain of 0.0079% for a specimen with 6.35 mm gage length. To further improve the accuracy, a pair of lock nuts were used to tighten the tensile specimen to the bars in an effort not only to prevent the specimen from potential pre-torsional deformation and damage during installation, but also to provide better thread engagement between the specimen and the bar ends. As a demonstration of this technique, dynamic tensile stress–strain response of a 304L stainless steel was characterized with high resolution in both elastic and plastic deformations.